Aseptic-clinical hand hygiene knowledge survey amongst health care workers in a tertiary care hospital in Western India - Vaishnav, Bhumika; Bamanikar, Arvind; Dasgupta, Sukanya; Reddy, Anudeep (International Journal of Research in Medical Sciences, 2016)
Background: Maintenance of hand hygiene among health care workers (HCWs) is the cornerstone of infection prevention and control programmes in a health care facility. Poor hand hygiene amongst HCWs is the single most common cause of cross-transmission of infections between patients and HCWs in the hospital. The objective of this study was to identify the risk factors for non-adherence and assess the knowledge regarding maintenance of hand hygiene amongst health care workers at a tertiary health care centre in Western India. Methods: A descriptive, cross-sectional study was conducted on HCWs - doctors, undergraduate students and staff nurses at a tertiary care hospital and post-graduate institute in western India after ethical committee clearance. A self-report questionnaire by the World Health Organisation (WHO) for the Hand Hygiene Knowledge Survey (2009), which consisted of ten questions and “My 5 moments of hand hygiene”, was answered by the study participants after their written/informed consent. Data was analysed using one-way Anova and Student’s t-tests. Results: 317 participants responded to the survey which included 131 doctors, 111 medical students and 75 staff nurses. 90.85% participants routinely used an alcohol-based hand rub (ABHR) but their overall hand hygiene knowledge score was only 61.04%. Prior formal training in hand hygiene significantly improved the knowledge of HCWs (P<0.001). There was a significant difference between the knowledge and actual practice of “My 5 Moments of hand hygiene”. Conclusions: Hand hygiene knowledge remains unsatisfactory till date amongst HCWs. There is a need to educate HCWs through frequent training session’s right from the time of undergraduate medical study.